The Influence of Green Knowledge on Purchase Intention Mediated by Green Lifestyle for Tumbler Products Among Generation Z in Bandung - Nadia Nurul Saadah; Eka Septiarini (LP2M IAIN Palopo, 2026)
The escalation of plastic waste in Indonesia, particularly in Bandung, indicates that the reliance on single use plastics continues to pose an environmental challenge that requires intervention. A potential measure to mitigate this issue is the utilization of reusable tumblers instead of single-use drinking vessels. Nonetheless, the adoption of reusable tumblers within an environmentally conscious lifestyle remains limited among Generation Z. This study aims to examine the influence of green knowledge on purchase intention mediated by green lifestyle, concerning reusable tumblers among Generation Z in Bandung. This research utilized a quantitative approach with a sample of 121 participants chosen through purposive sampling. The information for this research was gathered via an online survey disseminated through Google Forms, and it was determined to be both valid and reliable. Furthermore the data satisfied the traditional assumption evaluations necessary for hypothesis testing in this research, which included simple regression analysis, multiple regression analysis, and the Sobel test. The examination was performed using SPSS version 26. The findings demonstrate that green knowledge positively and significantly influences green lifestyle, green knowledge also positively and significantly influences purchase intention, furthermore, green lifestyle positively and significantly impacts purchase intention, and green lifestyle mediates the effect of green knowledge on purchase intention.